pengaruh Pengaruh Metode Bercerita Kisah Dalam Al-Quran Terhadap Akhlak Karimah Peserta Didik: Pengaruh Metode Bercerita Kisah Dalam Al-Quran Terhadap Akhlak Karimah Peserta Didik - Zulfa Fauziyyah; Sibilana, Annas Ribab (Gerasi Insan Nusantara, 2025)
This study was motivated by the researcher's desire to re-examine the theory of the storytelling method expressed by Poerwadarminta and Amin. In Poerwadarminta's theory, it is stated that the storytelling method can arouse the enthusiasm of students' learning in learning the morals of morals. It is hoped that by using this storytelling method, students can have a noble, ethical personality, and have good role models. While Samsul Munir Amin revealed that there are several praiseworthy characteristics of morals towards oneself, but in this study only discusses 3 characteristics, namely trustworthiness, forgiveness, and patience. The result of this study 1. There is no significant effect between the method of telling story the results of statistical calculations using the simultaneous test that fcount 0.595 < ftabel 3.287 with a sign level of 0.451> 0.05. Meanwhile, by using a partial test that tcount -0.772 < 1.753 with a sign level of 0.451> 0.05. So from these calculations it states that Ho is accepted and Ha is rejected, indicating that there is no significant influence between the method of telling stories in the Koran on the trustworthy nature of 4th grade students in moral teaching. 2. There is no significant effect between the method of telling stories in the Koran on the forgiving nature of students with the results of statistical calculations using the simultaneous test that fhitung 3.712> ftabel 3.287 with a sign level of 0.451> 0.05. Meanwhile, by using a partial test that tcount 1.927> 1.753 with a sign level of 0.451> 0.05. So from these calculations it states that Ho is accepted and Ha is rejected, indicating that there is no significant influence between the method of telling stories in the Koran on the forgiving nature of 4th grade students in moral teaching. 3. There is no significant effect between the method of telling stories in the Koran on the patient nature of students with the results of statistical calculations using the simultaneous test that fhitung 4.206> ftabel 3.287 with a sign level of 0.451> 0.05. Meanwhile, using the partial test that the tcount is 2.051> 1.753 with a sign level of 0.451> 0.05. So from these calculations it states that Ho is accepted and Ha is rejected, indicating that there is no significant influence between the method of telling stories in the Koran on the patient nature of 4th grade students in the learning of moral creed